Three-dimensional X-band SAR imaging of a small conifer tree - Morrison, Keith; Bennett, J. C.; Cookmartin, Geoff; McDonald, A. J.; Race, A.; Quegan, Shaun (Cranfield University, 2006)
High spatial resolution 3-D SAR imagery was recorded by the UK’s Natural Environment Research Council GB-SAR Microwave Measurement Facility at the University of Sheffield. X-band V V polarisation measurements were made using a near-field monostatic imaging system inside an anechoic chamber. The measurement process employs vector network analyser techniques to sample backscatteredsignals over a 2-D aperture, allowing a 3-D reconstruction of a target. This technique is used to provide a detailed 3-D map of the spatial scattering behaviour of a small Colorado Blue Spruce tree (Picea pungens glauca). The images produced are at a su“ ciently high spatial resolution ( ~ 5 cm) that individual plant components can be discerned. An ability to select any volume pixel from within the target allows features in the microwave reconstruction to be readily associated with structures in the tree. The scattering behaviour associated with the uppermost set of branches shows it to be dominated by scattering from the branch tips.